Religious Approach Methods In The Tanjung Gusta Special Children's Correctional Institution - Aulia Utari; Azizah Nur Khalisah Daulay; Hainun Hanifah; Sakhi Nabila Alhusna; Nashrillah MG (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research aims to find out the method of religiousness in juvenile correctional institutions toward religion, morals, and motivation. This approach method is used to help children in the prison system to improve their behavior throught religious values. The methods used can include individual guidance methods, group methods, direct methods and indirect methods. The religious approach in Tanjung Gusta special prison for children includes five daily prayers, practicing the sunnah of the prophet, some of the sunnah are performing sunnah prayers before the obligatory prayers, praying, morning and evening prayers. The author uses a qualitative approach method with the type of research and case study. The selection of subjects wa carried out using purposive sampling technique, which amounted to two people. The data collection method is carried out using interviews and observations so that it involves looking at the data as a whole to get an overview of the problem being studied.